Small manufacturing firms sustainable green practices: Operationalization of sustainable value framework - Yacob, Peter; Khor, Saw Chin; Jaganathan, Mathivannan; Maludin, Norliyana; Nodesan, Suresh (2018)
Traditionally, companies and the environment have continuously become two conflicting aspects, where business becomes an environmental risks, and environmental concern become threats to business expansion. However, in recent years, this conflict has progressively been side-lined with the development and implementation of sustainable green practices. The aim of this study is to identify what steps small manufacturing firms can take to successfully implement sustainable green practices into their operations. In order to achieve this, the study proposes the Sustainable Value Framework which is a generic framework through which firms are able to convert their sustainable undertakings into sustainable value. The data of this study was gathered from semi-structured interviews with five small manufacturing firm’s owners/managers. The findings shows that small manufacturing firms are challenged to strike a balance between the components of the SVF and status quo concerning firm’s current sustainable green practices. The findings also reveal that creating long term sustainable value from the implementation of sustainable green practices challenges small manufacturing firms to successfully operationalize considerations relative to each of the four quadrants of the Sustainable Value Framework. The imperial findings and practical implications offer an indicator encouraging other manufacturing firms to hop on the Go-green bandwagon, particularly those without any green practice in place.